In situ late triassic fossil conifer woods from the fluvial channel deposits of the Soturno River (Caturrita formation, Rio Grande do Sul, Brazil) - Crisafulli, Alexandra María Cristina (2016)
Fil: Crisafulli, Alexandra María Cristina. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.